2022
DOI: 10.3233/jad-215280
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Membrane Potential Influences Amyloid-β Protein Precursor Localization and Amyloid-β Secretion

Abstract: Background: Amyloid-β (Aβ), which derives from the amyloid-β protein precursor (AβPP), forms plaques and serves as a fluid biomarker in Alzheimer’s disease (AD). How Aβ forms from AβPP is known, but questions relating to AβPP and Aβ biology remain unanswered. AD patients show mitochondrial dysfunction, and an Aβ/AβPP mitochondria relationship exists. Objective: We considered how mitochondrial biology may impact AβPP and Aβ biology. Methods: SH-SY5Y cells were transfected AβPP constructs. After treatment with F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…A recent study suggested that the mitochondrial function determines Aβ release of the cells, and Aβ fluid levels and ratios might serve as biomarkers of mitochondrial integrity. 122 In our opinion, it seems unlikely that a protein or peptide would make such extreme changes in an organelle that did not function under physiological conditions.…”
Section: ■ Conclusionmentioning
confidence: 86%
“…A recent study suggested that the mitochondrial function determines Aβ release of the cells, and Aβ fluid levels and ratios might serve as biomarkers of mitochondrial integrity. 122 In our opinion, it seems unlikely that a protein or peptide would make such extreme changes in an organelle that did not function under physiological conditions.…”
Section: ■ Conclusionmentioning
confidence: 86%
“…In cytoplasmic hybrid (cybrid) cells, cell models allowing for the study of various effects of mitochondrial DNA (mtDNA) ( Wilkins et al, 2014 ), transferring mtDNA from patients with sporadic AD reduced ATP production and COX activity ( Khan et al, 2000 ; Cardoso et al, 2004 ) and increased ROS ( Cardoso et al, 2004 ) and Aβ ( Khan et al, 2000 ) production compared to mtDNA from age-matched controls. Mitochondria with low bioenergetic potential have increased APP translocation and express more Aβ, suggesting that APP targets these impaired mitochondria and that decreased fluid Aβ42/Aβ40 ratio may actually be a biomarker for impaired mitochondrial bioenergetics ( Wilkins et al, 2022 ). Increased Aβ production within the mitochondria also results in higher inner mitochondrial AICD, which is neurotoxic in a manner independent of Aβ ( Sandberg et al, 2022 ).…”
Section: Amyloid-β and Alzheimer’s Diseasementioning
confidence: 99%
“…Such hypotheses do not assume Aβ triggers the disease. Rather, it has been hypothesized that altered Aβ homeostasis, manifesting as either increased production or decreased clearance, may be an important AD biomarker that actually reflects impaired mitochondrial bioenergetics ( Wilkins et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…These data support the role of mitochondrial dysfunction in driving AD pathology and not vice versa, because systemic tissues lack amyloid plaques and neurofibrillary tangles, but mitochondrial deficits are present. Further studies directly support mitochondrial dysfunction in modulating tau phosphorylation, Aβ production, and the aggregation of both [ 25 , 26 , 27 ].…”
Section: Bioenergetics and Neurodegenerationmentioning
confidence: 97%
“…Decades of research link mitochondrial and bioenergetic stress with increased or decreased APP processing to Aβ [ 27 , 105 ]. More recently, mitochondrial membrane potential and, ultimately, mitochondrial activity were shown to directly influence the secretion of Aβ and the accumulation of intracellular Aβ [ 27 ]. Studies also directly link changes to mitochondrial function driving tau phosphorylation and accumulation [ 25 ].…”
Section: Consequences Of Disturbed Bioenergeticsmentioning
confidence: 99%